2015
DOI: 10.1177/096369351502400103
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of the Composite Laminates under Mechanical Loads with Different Layups using Different Plate Theories

Abstract: An analytical and numerical solution for general laminated composite plates under mechanical loading is presented based on different lamination plate theories (CLPT and FSDT). General lamination was evaluated by assumption of cross-ply and angle-ply laminated plates. In order to this, Navier-type method and simply supported boundary conditions for rectangular laminates are applied. As a verification method, a finite element code using ANS YS is also developed. Effects of lamination scheme, axial load direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When the unidirectional composite is in the principal axis direction, the elastic constant is calculated as follows. The relationship between the stress and the strain is given as [ 39 ]: where , , , , .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the unidirectional composite is in the principal axis direction, the elastic constant is calculated as follows. The relationship between the stress and the strain is given as [ 39 ]: where , , , , .…”
Section: Methodsmentioning
confidence: 99%
“…When the unidirectional composite is in the principal off-axis direction, the elastic constant is calculated as follows. The stress and strain have the following relationship [ 39 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Torabizadeh and Fereidoon [59] used CLPT and the first-order shear deformation plate theory (FSDT) to derive governing equations of the laminated composite plates. The results were shown that the fundamental frequency increased with the modular ratio for both cross-ply and angle-ply laminates with the CLPT.…”
Section: Author/referencesmentioning
confidence: 99%
“…The effect of cutout orientation β on buckling of the rectangular composite plate increases with increasing cutout size. Torabizadeh [60] presented a mechanical loading solution for generally laminated plates based on different plate theories of laminate. A finite element code was also developed as a verification method with ANSYS.…”
Section: Static Free Vibration and Buckling Analysis Of Composite Pamentioning
confidence: 99%